RANCANG BANGUN APLIKASI PENCATATAN HASIL TIMBANGAN TBS BERBASIS DESKTOP DI RUMAH ANGKUT MINYAK (RAM) - Erika Binjes Sagala; Ritna Wahyuni; Sri Lestari Rahayu (LPPM Universitas Abdurrab, 2026)
Oil palm plantations have an important role in supporting the national economy, especially through the production and distribution of Fresh Fruit Bunches (FFB). The weighing process is very important in the operational activities of the Oil Transport House (RAM) because it can determine the value of transactions and production reports. However, many RAM companies still use book-based manual logging systems, which often lead to logging errors, delays in compiling reports, and the risk of data loss. This condition shows that a computerized information system is needed to improve the accuracy and efficiency of recording weighing results. The purpose of this research is to create and develop a desktop-based application that can record the results of weighing FFB in RAM. The system was developed using the Waterfall model of the System Development Lifecycle (SDLC), which consists of planning, analysis, design, and implementation stages with data collection through literature studies, observations, and interviews. The application was developed using the Java NetBeans and MySQL database management systems, and uses data collection methods such as observation, interviews, and literature studies. The results of the study show that the application built is able to produce balance slip bonds, daily, monthly and annual reports, as well as automatically calculate transaction data. System testing using the Black Box Testing method shows that all application features can run according to the features designed and declared valid. Thus, the application developed is able to improve operational efficiency, reduce recording errors, speed up the reporting process, and support more effective processing of FFB balance data at Oil Transport Houses (RAM)